Importance of dosing: Analysis of touch-free hand hygiene dispensers for consistency. - Smith, Nicole M.; Bánsághi, Száva; Chen, Nanshan; Neal, Travis B.; McNulty, John J.; Haidegger, Tamás P.; Arbogast, James W. (American Journal of Infection Control, 2025)
We investigated 5 touch-free automatic foam alcohol-based handrub (ABHR) hand hygiene dispensers common in US hospitals. Output dosing was evaluated for consistency to comply with the Leapfrog 2022 guidance requirement of ≥ 1.0 mL per ABHR dispense. Fifteen dispensers and 32 distinct refills were tested, with > 10,000 dispenses analyzed for 5 different dispensing systems. Automated testing used computer programming and mechatronics to activate the dispensers and capture output weights at predetermined delay patterns. Low, medium, and high usage patterns per day were set with dispense delay patterns. In another laboratory, dispensers were activated manually for measurements; 50 doses were collected and weighed within an hour for each refill. Three of the dispenser systems had mean output > 1.0 mL, and 2 were < 1.0 mL. Two dispensers have significantly greater variability, which is driven by the foam pump design. It was discovered that usage/testing patterns impact dosing performance. The dispenser design and engineering cause significant differences in volume dispensed and consistency across dispenses. Using sufficient ABHR to cover hands completely and keeping hands wet long enough to significantly reduce pathogens is an important requirement. Facilities should assess ABHR dispenser outputs and consider consistent dosing as an essential performance criterion for effective hand hygiene policies and practices. • Some automatic foam dispensers provide less than 1 mL per dose on average. • Dispenser design and pump engineering impact dosing volume and dispense consistency. • Usage patterns (time delays between dispenses) can affect the avg. dispensed dose. • Companies should openly share the avg. volume and variation of their dispensers. • Facilities should prioritize consistent dosing for effective hand hygiene.